Species diversity and anti-hepatitis B virus activity of culturable bacteria isolated from the habitat of Bruguiera gymnorhiza - Shishi HOU; Kaoyun LIANG; Chenghai GAO; Cuiping JIANG; Qianqian TANG; Yonghong LIU; Xiangxi YI (Guangxi Zhiwu, 2023)
Mangrove habitat is rich in microbial flora and its secondary metabolites have novel structure, which is an important source for mining new drugs. This study preliminarily evaluated the culturable bacterial diversity of sediments, roots, leaves and hypocotyls of Bruguiera gymnorhiza and the biological activity of bacterial metabolites, and looked for anti-HBV drug source strains. Pure culture technique and 16S rRNA molecular biology technique were employed to determine the species of bacteria and analyze the species diversity. Using HepG2.2.15 cell line as a model, the anti-HBV activity of bacterial metabolites was tested by MTT and PCR techniques. The secondary metabolites of active bacteria were preliminary analyzed by LC-HRMS technique. The results were as follows: (1) A total of 59 species of bacteria were obtained, belonging to 4 phyla, 5 classes, 14 orders, 23 families, and 36 genera, among which Bacillus was the dominant genus. Strains GXIMD07402, GXIMD07665 and GXIMD07384 were potential new species of Pseudooceanicola, Thioclava and Aestuariibaculum, respectively. (2) The results of anti-HBV activity showed that GXIMD07366, GXIMD07616, GXIMD07384, GXIMD07550 and GXIMD07445X could significantly reduce the level of HBV DNA in the supernatant of HepG2.2.15 cells (P<0.05), and the inhibition rates were 51%, 47%, 63%, 52% and 47%. (3) Four main secondary metabolites of the highly active strain GXIMD07384 were preliminarily identified as Adenosine, Cyclo(L-Pro-L-OMet), Acremine G and 7,8-dimethylbenzo［g］pteridine -2,4(1H,3H)-dione. The results of the study confirm that the species diversity of culturable bacteria in the habitat of Bruguiera gymnorhiza is rich, and it contains strains that can produce anti-HBV active compounds, which provide a basis for the subsequent application of marine microbial resources.